Service Delivery Through Knowledge Management In Higher Education - Mathew, Viju (Journal of Knowledge Management Practice, 2010)
Service sector like higher education offers various programs to develop the students which can add value to the society. People, knowledge and technology plays vital role in attaining high service quality, economic development and growth. Managing these resource and capabilities supports the organization to create competitiveness among other rivals in the industry. Knowledge has being as core part to create human competence. Managing this power in the most effectively and efficiently leads the organization to attain competitive advantage leveraging the resources and capabilities for achieve its objectives. KM techniques and tools can be applied in higher education system improve academic services (teaching- learning process). This paper highlights some of the issue interlinking knowledge management with higher education service development giving a framework for adopting KM in higher education providing some of the KM based solution for higher education institution. The KM model indicates giving understanding about the approach to use appropriate development for providing service delivery and development in higher education.
Keywords: Knowledge management; Higher education; Service delivery